The Academy - Hilderbrand, Elin; Cunningham, Shelby (Little, Brown and Company, 2025)
"It's move-in day at Tiffin Academy and amidst the happy chaos of friends reuniting, selfies uploading, and cars unloading, shocking news arrives: America Today just ranked Tiffin the number two boarding school in the country. It's a seventeen-spot jump - was there a typo? The dorms need to be renovated, their sports teams always come in last place, and let's just say Tiffin students are known for being more social than academic. On the other hand, the campus is exquisite, class sizes are small, and the dining hall is run by an acclaimed New York chef. And they do have fun--lots of parties and school dances, and a piano man plays in the student lounge every Monday night.But just as the rarefied air of Tiffin is suffused with self-congratulation, the wheels begin to turn - and then they fall off the bus. One by one, scandalous blind items begin to appear on phones across Tiffin's campus, thanks to a new app called ZipZap, and nobody is safe. From Davi Banerjee, international influencer and resident queen bee, to Simone Bergeron, the new and surprisingly young history teacher, to Charley Hicks, a transfer student who seems determined not to fit in, to Cordelia Spooner, Admissions Director with a somewhat idiosyncratic methodology - everyone has something to hide. As if high school wasn't dramatic enough...As the year unfolds, bonds are forged and broken, secrets are shared and exposed, and the lives of Tiffin's students and staff are changed forever. The Academy is Elin Hilderbrand's fresh, buzzy take on boarding school life, and a thrilling new direction from one of America's most satisfying and popular storytellers."--Amazon